'Your Face Looks Backwards': Time travel cinema, nostalgia and the end of history. (December 2015) - Sweeney, David
In his Ghosts of My Life, Mark Fisher argues that in the 21st century Western culture is in a state of stasis, which 'has been buried, interred behind a superficial frenzy of "newness", of perpetual movement'. To substantiate this claim Fisher contrasts contemporary pop music, particularly that with a 'classic' sound – such as recordings by Adele, Amy Winehouse and Arctic Monkeys – with the pop of the 1970s and '80s, the 'mutations' of which enabled listeners of his generation to 'measure the passage of cultural time', concluding that today it is 'the very sense of future shock which has disappeared from' music and from culture generally. In this paper I apply Fisher's observations to science fiction cinema focusing, on three recent time travel movies – Sound of My Voice (2011), Looper (2012) and About Time (2013) – and arguing that only the first can truly be considered science fiction, even though its relationship to the genre is the most problematic, since it may not involve time travel at all, and that the others, where time travel is used unambiguously, are instead exercises in what I term 'genre-splicing' – the introduction of elements of one type of narrative to another – a process which, like the 'classic' pop sound, is an indication of the lack of a sense of the future in current Western culture. A key element of Sound of My Voice is the promise of a future in which the culture industry has been replaced by an authentic folk culture; while this may appear merely a nostalgic fantasy, also identifiable in Looper 's fetishism of aspects of the Old West and the use of 'nu-folk' on About Time 's soundtrack, I argue, drawing on Walter Benjamin's writings on nostalgia, that the Sound of My Voice 's representation of a 'folk future' is not an escapist fantasy but, like the uncertainty of the film's generic status, a provocation, which asks us to reconsider our relationship both to contemporary capitalism and to the future which can be made to happen.